1994
DOI: 10.1071/ch9940111
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur- and Carbon-Bonded Forms of the Cobalt(III) Complex With the Ligands 2-Aminoethyl 3-Aminopropyl Sulfide and 1,1,1-Tris(aminomethyl)ethane

Abstract: The new sulfur-bonded compound [Co(tame)( aeaps )] Cl3.H2O has been synthesized by the reaction of aeaps with Co(tame)Cl3 [tame = 1,1,1-tris( aminomethyl )ethane, and aeaps = 2- aminoethyl 3-aminopropyl sulfide or 3-thiahexane-1,6-diamine]. The Co(tame)( aeaps )3+ ion equilibrates in basic solution with the corresponding carbon-bonded species: Co(tame)( aeaps )3++HO-↔ Co(tame)(C-aeaps )2++H2O A salt of the carbon-bonded species, [Co(tame)(C- aeaps )](S2O6), has been isolated and its structure solved by X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…Subsequently, a series of cobalt(III) coordination compounds with C-aeaps has been studied, in which C-aeaps occupies one octahedral face, while the other face has been occupied by ligands like 1,4,7-triazacyclonane (tacn) or tris(1-aminomethyl)ethane (tame) to simplify the observed reactions by avoiding different isomers. In these studies, it was shown that there is an equilibrium between the sulfur-bound form [CoL(aeaps)] 3+ and the carbon-bound form [CoL(C-aeaps)] 2+ , and the structural, equilibrium, and kinetic parameters for the systems with L = tacn or L = tame have been determined …”
Section: Introductionsupporting
confidence: 71%
“…Subsequently, a series of cobalt(III) coordination compounds with C-aeaps has been studied, in which C-aeaps occupies one octahedral face, while the other face has been occupied by ligands like 1,4,7-triazacyclonane (tacn) or tris(1-aminomethyl)ethane (tame) to simplify the observed reactions by avoiding different isomers. In these studies, it was shown that there is an equilibrium between the sulfur-bound form [CoL(aeaps)] 3+ and the carbon-bound form [CoL(C-aeaps)] 2+ , and the structural, equilibrium, and kinetic parameters for the systems with L = tacn or L = tame have been determined …”
Section: Introductionsupporting
confidence: 71%
“…Furthermore, reacidification of a sample of the deprotonated species dissolved in D 2 O with concentrated DCl (after 24 h) gave quantitative recovery of the parent complex with no sign of any C-H exchange, or Co-C bond formation, as has been reported for [Co([9]aneS 3 ) 2 ] 3+ , 17 and for a number of mixed N-S donor systems. [18][19][20][21][22][23] The C-H bonds adjacent to the coordinated thioethers in [Co(Me 2 -N 3 S 3 sar)] 3+ do not have the appropriate orientation for the stabilization of a carbanionic species through a dπ-pπ interaction, and the structure is considerably more rigid than the linear tridentate ligands for which such deprotonations have been reported. The secondary N-H protons in [Co(Me 2 -N 3 S 3 sar)] 3+ are significantly more acidic than those in ordinary cobalt(III) secondary amines, in line with that reported for the N 6 cages.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26] Despite the ready deprotonation of a coordinated amine center in the N 3 S 3 cage complex, the lack of S-CH 2 proton exchange (assisted by amine deprotonation) is consistent with the reported stereospecificity of this process. [20][21][22][23] The [Co(Me 2 -N 3 S 3 absar)] 3+ complex shows the expected lack of symmetry in the 13 C NMR spectrum arising from the lack of a methylene unit in one strand of the cage. The 1 H NMR spectrum again shows two singlets for the apical methyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…An unusual route for the preparation of alkylcobalt(III) compounds is the coordination of the carbanion formed by the reversible deprotonation of an S-bonded methylene group in thioethercobalt(III) compounds (see Scheme below). This method has proved feasible in a number of cases where aminoethyl aminopropyl sul®de (aeaps, 3-thiahexane-1,6-diamine) occupies one face of the octahedron in six-coordinate cobalt(III) compounds (Bjerrum et al, 1988;Kofod et al, 1994). The opposite face of the octahedron was blocked by the neutral amine ligands 1,4,7-triazacyclononane (tacn) or 1,1,1-tris(aminomethyl)ethane (tame), or by a second aeaps ligand.…”
Section: Commentmentioning
confidence: 99%
“…the 1,6-diamino-3-thiahexan-4-ide anion, C-aeaps, have been reported. The X-ray crystal structures of [Co(tame)(C-aeaps)]S 2 O 6 and [Co(tacn)(C-aeaps)](ClO 4 ) 2 both suffered from severe disorder of the cation Kofod et al, 1994). In both cases, the disorder was explained by the two chelate rings of C-aeaps being partly interchanged.…”
Section: Commentmentioning
confidence: 99%